A new species of the genus Chondromorpha Silvestri, 1897 and a catalogue of Paradoxosomatidae Daday, 1889 millipedes from Gujarat, India, along with their distributions and ecological perspectives (Diplopoda, Polydesmida, Paradoxosomatidae) - Dave, Ridham; Sindhav, Gaurang (Zootaxa, 2025)
This study examines Paradoxosomatidae Daday, 1889 millipedes in Gujarat, India, focusing on taxonomic diversity, distribution patterns, and behaviours. It highlights a new species, Chondromorpha lakroda sp. nov., along with five known species. The study observed intriguing behaviours such as swarming, and escape mechanisms, indicating adaptive strategies for predator protection and resource acquisition. The discovery of C. lakroda sp. nov. in sandy loam soil near the river Sabarmati highlighted unique characteristics contributing to their survival and defensive capabilities. This study enhances our understanding of paradoxosomatid species distributions in Gujarat and emphasizes the ecological significance of millipedes as ancient soil invertebrates. Further research should thoroughly explore their diversity and ecological contributions in terrestrial ecosystems.